IMPROVING ENGLISH WRITING SKILL OF ELEMENTARY STUDENTS BY USING WHAT’S MISSING METHODS - Ade Christianti; Dayu Retno Puspita; Ahmad Arif Fadillah (UIBU, 2019)
This study aims to determine the effect of students' writing skills on English subjects using the 'What Missing' method. This study used a quasi-experimental research method with the research design of Nonequivalent Control Group Design. The population subjects in this study were 76th grade students of Kampung Melayu 1 Elementary School 1 Tangerang Regency. Data collection techniques using question instruments test essay writing skills To test the pretest hypothesis in this study used the t test, from the results of the t test obtained t count = -0.3 <t table = 2.00. Whereas for testing the posttest hypothesis from the results of the t test it is obtained t count = 6.06> t table = 2.00, it can be concluded that there is a significant effect between the posttest value of the control class and the experimental class. This can be interpreted that the use of the What’s Missing method is very influential on students' English writing skills.